ANALISIS HUBUNGAN DAN PENGARUH FAKTOR-FAKTOR BERKONTRIBUSI TERHADAP KINERJA MUTU PROYEK KONSTRUKSI JALAN DI PROVINSI ACEH - T. Ferdian; M. Isya; Hafnidar A.Rani (Prodi Magister Teknik Sipil Unsyiah, 2018)
The quality performance of road improvement and road development projects in Aceh Province has always been highlighted by various elements of society. This is due to the occurrence of the damage that the age of the plan has not timed. It is also often found quality mismatch so that road construction must be dismantled and reworked. This study aims to analyze the relationship and influence between the factors that contribute to the quality performance of road construction projects, and to identify the dominant factors affecting the quality performance of road construction projects in Aceh Province. This study used qualitative methods quantized through questionnaires. The number of research samples obtained by 75 companies. The sampling technique used is purposive sampling with the consideration of the contractor company that has completed the road construction project in Aceh Province from 2010-2015. Independent variables consist of human resource, material, equipment, evaluation, managerial, finance, field management, project owner, design, and environment, while the dependent variable is the quality performance of road construction project. Statistical analysis used is reliability test, descriptive analysis, simple correlation and multiple linear regression using Statistical Product and Service Solution (SPSS) version 22 software. The results show that human resource, material and equipment factors have very low relation, evaluation factor and managerial have low relation, finance factor have good relation, environment factor have high relation, while management and design factor have very high relation to quality performance at road construction project in Aceh Province. Contributing factors that affect the quality performance of road construction projects in Aceh Province are the factors of management, and design. The dominant factor affecting quality performance in road construction project in Aceh Province is management factor. This indicates that if the management factor is improved by the contractor then the quality performance of the road construction project will increase.